2021
DOI: 10.1111/jocn.15995
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceptions of stroke patients living with dysphagia: A qualitative meta‐synthesis

Abstract: Aims To systematically review and synthesise the findings of qualitative research exploring experiences of dysphagia from stroke patients' perspectives. Background Poststroke patients with dysphagia are suffering from impaired physical functions and heavy psychological burden, and they are living with compromised quality of life. Through synthesising qualitative studies to fully portrait the experiences of poststroke patients living with dysphagia, we can care better for this population. Design A systematic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
(109 reference statements)
1
9
0
Order By: Relevance
“…Our findings are similar to those of previous studies conducted in Western countries for how community‐dwelling older adults adjust to living with dysphagia (Howells et al, 2021; Li et al, 2022). We found that NH residents adjusted to the irregular cough resulting from dysphagia by making sure they had some sort of liquid available, cutting food into smaller pieces, eating more slowly or having someone pat them to avoid choking.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are similar to those of previous studies conducted in Western countries for how community‐dwelling older adults adjust to living with dysphagia (Howells et al, 2021; Li et al, 2022). We found that NH residents adjusted to the irregular cough resulting from dysphagia by making sure they had some sort of liquid available, cutting food into smaller pieces, eating more slowly or having someone pat them to avoid choking.…”
Section: Discussionsupporting
confidence: 92%
“…A qualitative meta‐synthesis of five qualitative studies on stroke patients with dysphagia identified five themes describing their experiences: life changes after dysphagia, coping with social events, rebuilding a normal life and limited professional services (Li et al, 2022). The authors suggested management of psychological and physical health was needed for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication between patient and provider is imperative to minimize this medical burden and reduce uncertainty. It is recognized that patients lack the knowledge to self‐manage their dysphagia, and they also encounter difficulty obtaining adequate information about their dysphagia from healthcare providers 12 . QPLs have the potential to facilitate effective patient‐physician communication and provide the opportunity for improved patient experience and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, qualitative research evidence has not been fully synthesized and analyzed. Quantitative systematic reviews emphasize the quantification of effects and relationships [such as correlations ( 30 ), acceptability ( 31 ), or the aggregation of influencing factors ( 32 )], while qualitative systematic reviews prioritize the exploration and understanding of complex phenomena [such as experiences ( 33 ), perspectives ( 34 ), or coping strategies ( 35 )]. Therefore, this study aims to analyze, from the perspective of nursing staff, the challenges and coping strategies faced in their work through the synthesis and integration of existing evidence.…”
Section: Introductionmentioning
confidence: 99%